Is There any Association Between CagA+ H. Pylori Infection and Histopathological Types of Gastric Carcinoma (Medicine Today, 2012)
Enormous studies have been conducted worldwide regarding CagA+ status of H. pylori in gastric carcinoma. But no study relating CagA+ status and gastric carcinoma has been carried out in our country yet. Thus, this study has been designed to see the association between CagA+ H. Pylori infection and histopathological types of gastric carcinoma. For this purpose, a total number of 80 (eighty) patients were selected. Of the 80 (eighty) patients 40 (forty) were selected as cases (malignant) and the remainder 40 (forty) were selected as controls (non-malignant). H. pylori was detected by applying non-invasive (H. pylori IgG serology and CagA IgG serology) and invasive (Histology and rapid urease test) technique. Of them Histology was done by Modified giemsa stain which was regarded as gold standard, CagA IgG was detected by ELISA method. Study reveals that there is no significant difference between histologic sub-types (Intestinal vs. Diffuse) of gastric carcinoma in relation with H. pylori positivity and present study also shows that there is no significant difference among the sites of lesion regarding H. pylori positivity. In this study, we see that among the 40 cases, 35(thirty five) possess the CagA+ H. pylori strain. And among the 40 controls, 33(thirty three) bear the CagA+ H. pylori strain. Here case-control difference is insignificant regarding CagA IgG status.The present study supports the view of an association of H. pylori infection with both intestinal and diffuse types of gastric cancer. It may be possible that H. pylori may be causally related to both forms of gastriccancer via unknown mechanism or this finding may be due to small sample size. In this study, no significant difference between case and control on the point of CagA IgG status was found. There are sufficient papers in favor of it-which argues that CagA positivity as well as H. pylori positivity is not the sole causative agent of gastric carcinoma. If so,it merely acts as an initiator.However,it is being left open for the future researchers to prove or to disprove it. Medicine Today 2010 Volume 22 Number 02 Page 62-69 DOI: http://dx.doi.org/10.3329/medtoday.v22i2.12435